(untitled) (Annals of Medical Research, 2023)
Aim: It was aimed to evaluate the characteristics of the patients who were referred to our electroneuromiyography (ENMG) Laboratory to evaluate the rate of locomotor system disability from the Disabled Health Board (DMB). Materials and Methods: Patients aged 18 years and over who applied to our hospital’s DMB in the last three years (01.01.2019-31.12.2021) and were referred to the ENMG Laboratory to determine the disability rates related to the locomotor system were included. With the retrospective analysis, demographic characteristics of the patients, ambulatory levels, etiological factors, reasons for applying to the ENMG Laboratory, and diagnoses in ENMG reports were noted. Results: Files of 1306 patients were reviewed, ENMG was performed in 139 (10.64%). The mean age was 45.34±12.2 years. One-hundred and eleven (79.9%) patients were male and 28 (20.21%) were female. Eighteen (12.9%) of the patients needed an assistive walking device. The most common etiological factors in locomotor system disability was disc herniation in 24 (17.2%) patients. The most common preliminary diagnosis was peripheral nerve injury in 67 (48.2%) patients. Peripheral nerve injury was the most frequently reported pathology in ENMG reports with 52 (37.4%) patients. While the ENMG report of 26 (18.7%) patients was normal; entrapment neuropathy was found in 14 (10.1%) patients, polyneuropathy in 10 (7.2%) patients, plexopathy in 8 (5.8%) patients, and cranial neuropathy in 1 (0.7%) patient. Conclusion: Peripheral nerve injuries are the most common pathology in both preliminary diagnosis and ENMG reports. ENMG provides information such as the location and the severity of the lesion, so electrodiagnostic tests are very important in the evaluation of locomotor system disability.